Estrianna gen. nov. (Hemiptera, Cicadellidae, Neobaliinae) e descrições de três novas espécies - Zanol, Keti M. R. (Acta Biológica Paranaense, 2012)
<htm>Estrianna gen. nov. (Hemiptera, Cicadellidae, Neobaliinae) e descrições de três novas espécies </htm>